Feedlot performance and immune function analysis of implanted and non-implanted steers selected for alcohol dehydrogenase 1 C (ADH1C) genotype and fed a low vitamin A diet. (18th June 2018) - Madder, K. M.; McKinnon, J. J.; Torres, G. W.; Krone, K. G.; Duncombe, J. L.; Luby, C. D.; Buchanan, F. C.
Abstract : Previous studies have shown that the interaction between limiting vitamin A (VA) and an alcohol dehydrogenase 1 C ( ADH1C ) variant in beef cattle results in increased intramuscular fat in the longissimus thoracis muscle in one genotype when fed low dietary VA. Although quality grade is important for increased profitability and improving taste characteristics of beef products, limiting VA too drastically can impair animal welfare. The objectives of this study were to determine if this marker-assisted management strategy would be effective, and whether any impairment in immune function would occur in a feedlot setting. Mixed breed beef steers ( n =2000) were sorted into 40 feedlot pens so that all combinations of ADH1C genotype ( TT or CT ), VA level (50% or 100% of recommended) and hormonal implant status (implanted (IMP) or non-implanted (NI)) were equally represented within the population. The VA× ADH1C interaction was not observed. An implant status × ADH1C interaction was observed with average daily gain (ADG; P =0.03). Steers that were IMP and CT had higher ADG than IMP TT ( CT =1.69 and TT =1.62 kg/day), whereas both genotypes in the NI steers were lower ( CT =1.29 and TT =1.32 kg/day). Implant status was shown to affect dry matter intake (DMI; IMP=8.55 and NI=7.87 kg; P <0.01), total days-on-feed (IMP=164.4 and NI 210.5 days; P <0.01), USDA yield grade (YIELD; IMP=2.40 and NI=2.77; P <0.01), marbling score (MARB; IMP=392 and NI=455; P <0.01), longissimus thoracis area (LTA; IMP=85.0 and NI=80.7 cm 2 ; P =0.01) and backfat thickness (FAT; IMP=8.0 and NI 10.0 mm; P <0.01). Overall, IMP animals finished on fewer total days-on-feed with higher ADG, DMI, larger LTA, and lower YIELD, MARB and FAT. To investigate immune function parameters, crossbred steers ( n =18) were selected from a prior feeding trial so that all combinations of ADH1C ( TT, CT and CC ) and VA (25% or 75%) were equally represented. Blood cell count analysis and peripheral blood mononuclear cell proliferation and stimulation assays were conducted. None of these immune parameters were affected by VA level. Treatment and mortality records were examined in the 2000 steer population, where no correlations with ADH1C, implant status or VA level were observed. Due to no VA × ADH1C interaction, this nutrigenetic marker-assisted management strategy is not effective at this time in commercial beef cattle feedlots, however, supplementing VA at a level as low as 25% of recommended in finishing rations would likely not result in signs of immune dysfunction.